O relato: uma experiência humana na linguagem inscrita nos atos de relembrar, contar e reconstruir memórias - Bourscheid, Catiúcia Carniel Gomes (2020)
This work deals with the human experience of the subject with language, defending the thesis that the human experience, demarcated in the oral report, which occurs in the passage from speaker to subject of the enunciation, reveals cultural elements that mark the relationship of the human being with the world. The thesis presents a linguistic foundation anchored in the studies of the linguist Émile Benveniste, especially those aimed at the presence of man in the language. The writing is based on the benvenistian reflections presented in the two volumes of the Problems of General Linguistics, having as basic text The Formal Apparatus of Enunciation (1970). Contemplating an interdisciplinary character present in this research, a debate is promoted among different authors, especially in the areas of Philosophy, Anthropology and History, through wich research is based within Human Sciences. The reflections promoted by Dany Robert-Dufour (2000), Paul Ricoeur (2007 and 2010) and Giorgio Agamben (2008) stand out. The hypothesis that guides the research is that: the human experience with language reveals the world of the men who use it. Faced with this, the general objective of the study is to understand how the subject (re)constitutes their human experience through speech when evoking memories and (re)telling them through a report. Therefore, our research is qualitative. The investigative path was guided by the following specific objectives: a) analyzing reports from residents of the city of Passo Fundo / RS; b) perceiveing how these subjects pass from speakers to subjects of their enunciations; c) observing the relationship of the subjects with time and how this is made explicit in their speeches; and d) observing what the subjects say about themselves and society from what they enunciate. Methodologically, the analysis procedures result from a bibliographic review, from which concepts are mobilized to be explored in observance of the corpus selected for this study: oral reports bound to the project Listening to memory: Passo Fundo and its stories, produced by the Oral Memory and Image Laboratory of the Graduate Program in History at the University of Passo Fundo. As part of the conclusions, it is observed that the oral narrative is a source of memory capable of presenting the complexity of man's relations with the world, and should be considered a heritage of society. Furthermore, it is observed that it is through language, manifested by the appropriation of language, that it is possible to understand the subject and the society in which they are inserted. Subject, language and society are so imbricated that they can only be conceived in their coexistence.